EFFICACY OF DIFFERENT FUNGICIDES FOR THE MANAGEMENT OF CHILLI ANTHRACNOSE CAUSED BY COLLETOTRICHUM CAPSICI - Y. B. CHAUHAN,; R. L. PATEL,; R. F. CHAUDHARY,; N. K. RATHOD, (The Bioscan, 2014)
Chilli (Capsicum annum L.) is an important spice cum vegetable crop. Among various diseases, anthracnose caused by Colletotrichum capsici is a major problem in India. All the fungicidal treatments were significantly superior over control in checking the anthracnose disease intensity in both individual year and pooled data. Minimum disease intensity of 19.67 % was recorded in carbendazim 0.05 % which was statistically at par with spraying of 0.2 % mancozeb (20.71 %), 0.2 % carbendazim + mancozeb (22.51 %) and 0.2 % copper oxychloride (23.16 %). Maximum fruit yield of 3383.47 kg/ha was recorded with three sprayings of carbendazim 0.05 % which was statistically at par with mancozeb 0.2 % (3317.54 kg/ha) and carbendazim + mancozeb 0.2 % (3103.76 kg/ha). The economics of different treatments revealed that carbendazim 0.05 % or mancozeb 0.2 % sprayed at 15 days interval starting from the appearance of the disease was most effective for the control of anthracnose disease of chilli and get higher healthy fruit yield and cost benefit ratio.